2022
DOI: 10.1136/bmjopen-2021-052130
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 RBD-specific and NP-specific antibody response of healthcare workers in the westernmost Austrian state Vorarlberg: a prospective cohort study

Abstract: ObjectivesAustria, and particularly its westernmost federal state Vorarlberg, developed an extremely high incidence rate during the COVID-19 pandemic. Healthcare workers (HCWs) worldwide are known to have an increased risk of contracting the disease within the working environment and, therefore, the seroprevalence in this population is of particular interest. We thus aimed to analyse SARS-CoV-2-specific antibody dynamics in Vorarlberg HCWs.DesignProspective cohort study of HCWs including testing at three diffe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In our Austrian HCW groups, which included environmental services and allied health professionals, 7.7% of the participants had IgG antibodies against SARS-CoV-2, indicating relevant prior contact with the virus. In comparison, the percentage of SARS-CoV-2 seropositive HCWs rose to 14% in the south-western parts of Austria, which were most affected by the pandemic [22] . The general SARS-CoV-2 seroprevalence for Austria was estimated to be 4.7% by April 2021 (Statistic Austria Report; [23] , [24] .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In our Austrian HCW groups, which included environmental services and allied health professionals, 7.7% of the participants had IgG antibodies against SARS-CoV-2, indicating relevant prior contact with the virus. In comparison, the percentage of SARS-CoV-2 seropositive HCWs rose to 14% in the south-western parts of Austria, which were most affected by the pandemic [22] . The general SARS-CoV-2 seroprevalence for Austria was estimated to be 4.7% by April 2021 (Statistic Austria Report; [23] , [24] .…”
Section: Discussionmentioning
confidence: 89%
“…The authors of these reports concluded that the differences in seroprevalence resulted from the availability of and compliance to respective precaution measures [25] . Other authors reported that, with increasing community infection numbers, the seroprevalence of SARS-CoV-2 in HCWs rose similarly [22] , [26] . In our study, we aimed to describe risk factors regarding occupational safety and health in our specific HCW groups.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation